PENGARUH PERTUMBUHAN PENDUDUK TERHADAP PERMINTAAN RUMAH DI KOTA PEKANBARU - Arjulita, Mira; Chalid, Nursiah; Indrawati, Toti (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Ekonomi, 2014)
Housing as one of the basic needs that must be met by the public as well as determine the level of social welfare. Demand for residential or housing is closely linked to population growth. This research aims to determine and analyze the effect of population growth on the demand for homes at Pekanbaru. Methods of analysis used is a simple linear regression. For purposes of analysis used secondary data time series, 2001-2012, is demographic data and housing data at Pekanbaru. Statistical tests include the t test,correlation coefficient, and R-square (coefficient of determination). The results of this research indicate that population growth does not significantly affect the demand for homes at Pekanbaru is based on the significant t values greater than 0.05. Based on estimates ofthe regression coefficient of determination was found the R-Squared of 0.110 which shows that population grow thcan only explain or influence the demand of 11.00 percent and the remaining 89.00 percentase influenced by variables other than the variable of population growth. So expect to other similar research to complement well with adding variables or data are used so as to provide better results.Keyword: housing demand, population growth